PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE TERHADAP CUSTOMER LOYATY DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI - Muhammad Abyan Ramadhana; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This research discusses about how artificial intelligence and brand image influence customer loyalty on Tokopedia application users in South Jakarta, the Special Capital Region of Jakarta, Indonesia. The objective of this quantitative study is to test and analyse the influence of artificial intelligence on customer loyalty, the influence of artificial intelligence on brand image, the influence of brand image on customer loyalty, and the influence of artificial intelligence on customer loyalty with the mediation of brand image in the context of Tokopedia application users in South Jakarta, the Capital Region of Jakarta, Indonesia. This study is a quantitative study. Using purposive sampling technique, 103 people of South Jakarta, the Capital Region of Jakarta, Indonesia were selected as the respondents. The analysis were conducted by utilizing PLS (Partial Least Square), performed in SmartPLS 3. This study finds that artificial intelligence positively and insignificantly influences customer loyalty, that artificial intelligence positively and significantly influences brand image, that brand image positively and significantly impacts customer loyalty, and that brand image mediates the relationship between artificial intelligence and customer loyalty.